Observations of the West African Rainbow lizard from Ghana feeding on bread - Ofori, B.Y.; Martey, P.; Attuquayefio, D. (Herpetology Notes, 2018)
The West African Rainbow lizards are considered generalist insectivores, but recent studies suggest that they may be opportunistic feeders. Here we provide the first documented report of a Rainbow lizard feeding on white bread.